Macrophyte landscape modulates lake ecosystem‐level nitrogen losses through tightly coupled plant‐microbe interactions. (19th October 2015) - Vila‐Costa, Maria; Pulido, Cristina; Chappuis, Eglantine; Calviño, Adelina; Casamayor, Emilio O.; Gacia, Esperança
Abstract: Root functional diversity of submerged vegetation exerts a major effect on nitrogen (N) cycling in lake sediments. This fact, however, is neglected in current N‐balance models because the links between the engineering role of plants and in situ microbial N cycling are poorly understood. We hypothesized that macrophyte species with high root oxygen loss (ROL) capacity promote the highest denitrification because of a higher abundance of ammonia oxidizers and tighter coupling between nitrifiers and denitrifier communities. We sampled five small ultraoligotrophic shallow lakes with abundant macrophyte cover including sediments dominated either by Isoetes spp. (high ROL), mixed communities of natopotamids (low ROL), and unvegetated sandy sediments. At each site, we quantified denitrification (DNT) rates and proxies for the abundance of denitrifiers ( nirS and nirK genes), and both ammonia oxidizing archaea (AOA) and ammonia oxidizing bacteria (AOB) and the diversity of nirS ‐harboring bacteria. Vegetated sediments showed significantly higher abundances of N‐cycling genes than bare sediments. Plant communities dominated by Isoetes generated sediments with higher redox and NO 3 − concentrations and significantly higher DNT rates than natopotamids‐dominated landscapes. Accordingly, increasing DNT rates were observed along the gradient from low ROL plants‐bare sediments‐high ROL plants. Significantly higher abundance of the archaeal amoA gene was recorded in sediments colonized by high ROL plants unveiling a key biogeochemical role for AOA in coupling macrophyte landscape and ecosystem denitrification.